Peningkatan Produksi 8-Hydroxy 9,12-Octadecadienoic Acid (8-HODE) dari Kapang Endofit Curvularia lunata BioMCC Fe-00283 dengan Optimasi Media Fermentasi - WAHONO SUMARYONO; VINDYATRI WIDAYANTI; ERWAHYUNI ENDANG PRABANDARI (Fakultas Farmasi Universitas Pancasila, 2014)
8-Hydroxy 9,12-octadecadienoic acid (8-HODE) is an oxidized aliphatic fatty acid belongs to the group of oxylipins, which shows bioactivity. It was reported previously that Curvularia lunata BioMCC FE-00283, an endophytic fungi from Cibotium barometz be able to produce 8-HODE by submerged fermentation. Glucose, monosodium glutamate, corn oil are media components which showed significant effect toward HODE production by C. lunata BioMCC FE-00283. In this study we reported the enhancement of 8-HODE production by adding potato extract to previouse medium. These four medium components, which were potato extract, glucose, monosodium glutamate and corn oil, were optimized for 8-HODE production by Response Surface Metodology (RSM). A full factorial Central Composite Design (CCD) was used to explain the interaction effect between media components. Maximum HODE production predicted by the quadratic model was 16.46 mg/L where media composition consits of 36.50% potato extract, 3.60 g/L glucose, 15.92 g/L monosodium glutamate and 0.96 ml/L corn oil. Experimentally verification using these medium composition production of 8-HODE reached 16.189 ± 0.526 mg/L. This optimization,which was added potato extract as variabel in medium optimization was enhanced 3 times fold of 8-HODE concentration compare to the 3 variabel optimization.